(untitled) (IIUC Business Review, 2022)
The study examined the Green Human Resource Management (GHRM) practices that are significantly influential to the sustainable environmental performance of organizations. The study employed a quantitative method to analyze data, collected from 143 HR professionals of different establishments from ready-made garments & steel industries in Bangladesh. The purpose of the study is to investigate the connection and impact of GHRM practices on organizational sustainable environmental performance, to an extent, to identify the degree of the factor’s stimulus sustainability. Following previous works on this area, the study has revealed significant impacts of green reward & incentives, green training & development, green performance & management, and knowing green HRM, green organizational culture, and insignificant impact of green recruitment & selection on the sustainable environmental performance of organizations. The findings of the study might help HR managers and leaders in the organization by providing a constructive view of HR management practices. Furthermore, the contribution of this paper lies in enriching the scope and depth of green HRM in the emerging sustainable environmental performance of organizations. IIUC Business Review Vol. 7-8, Dec. 2018-19 pp. 123-146